Effect of Irradiation Area and Delay Time Processing On Exposure and Deviation Index Computed Radiography AGFA Series CR10-X - Pramartha, I Gede Erix Krisna Adi; Ratini, Ni Nyoman; Irma Wulandari, Putu (BULETIN FISIKA, 2021)
Abstract – Research has been carried out to determine the effect of irradiation area and delay time processing on the exposure index (EI) and deviation index (DI) of computer radiography (CR). The tools used are phantom skull, imaging plate (IP), grid, and CR. The exposure factor used is set constant. To find out the EI value, exposure was carried out with the following variations of the irradiation area, 25 cm x 25 cm, 25 cm x 28 cm, 28 cm x 30 cm, 30 cm x 36 cm and 30 cm x 43 cm. Then the exposure was carried out using a constant irradiation area of ??25 cm x 25 cm, but the delay time processing variations were carried out as follows, 5, 10, 15, 20, 25 minutes. The EI value is used to find the DI value. Next, a graph is made and a test is carried out in the form of a regression test to determine the relation between the area of ??irradiation on EI and delay time processing on EI. Path analysis was also carried out to determine the relation between the area of ??irradiation to DI and delay time processing to DI. The results of the regression test showed that the irradiation area and delay time processing had a significant effect on EI. The results of the path analysis test show that the area of ??irradiation has no significant effect on DI, while delay time processing and EI have a significant effect on DI. Key words: Exposure index, deviation index, delay time processing, irradiation area, computed radiography